Microscale interaction between laser and metal powder in powder-bed additive manufacturing: Conduction mode versus keyhole mode. (October 2019) - Wang, Hongze; Zou, Yu
Highlights: We have applied the VOF method to visualize the fusion of Ti-6Al-4V powders during laser irradiation in both conduction mode and keyhole mode. We have revealed the heat and mass balance in the two typical printing modes. The keyhole mode exhibits a larger printable powder-layer thickness than the conduction mode. The thermal distribution during the multiple-track printing in conduction mode is more uniform than that in keyhole mode. Abstract: Metal additive manufacturing (AM) techniques, particularly laser powder-bed methods, have shown tremendous advantages for producing high-value, complex, and customized components. However, precisely controlling the microstructure and defects of the products in the AM process has been a long-standing issue. Here, we have developed a coupled thermal-mechanical-fluid model to reveal the microscale dynamic evolution of metal powders, particularly for Ti-6Al-4V, during laser irradiation. Using different laser powers, layer thicknesses, and hatch spacings, we have systematically compared powder evolutions in two typical processing modes – conduction mode and keyhole mode. We have revealed the heat and mass balance in these two typical printing modes for the first time. There is only one circular flow in the longitudinal section of the molten pool in the conduction model, while two circular flows present in the keyhole mode. Gravity drives the melted metal to fill the gaps between the powders and contributes to the formation of the molten pool. The simulation results demonstrate that a larger printable powder layer thickness is achieved in the keyhole mode than that in the conduction mode. The thermal distribution during the multiple-track melting in the conduction mode is more uniform than that in the keyhole mode, leading to more uniform resulting microstructure. This study presents opportunities to control the microstructure and defects at the microscale of the AM products by modulating processing parameters and switching between conduction and keyhole modes.